Droplet ejection and sliding on a flapping film - Chen, Xi; Doughramaji, Nicole; Betz, Amy R.; Derby, Melanie M. (My University, 2017)
Water recovery and subsequent reuse are required for human consumption as well as industrial, and agriculture applications. Moist air streams, such as cooling tower plumes and fog, represent opportunities for water harvesting. In this work, we investigate a flapping mechanism to increase droplet shedding on thin, hydrophobic films for two vibrational cases (e.g., ± 9 mm and 11 Hz; ± 2 mm and 100 Hz). Two main mechanisms removed water droplets from the flapping film: vibrational-induced coalescence/sliding and droplet ejection from the surface. Vibrations mobilized droplets on the flapping film, increasing the probability of coalescence with neighboring droplets leading to faster droplet growth. Droplet departure sizes of 1–2 mm were observed for flapping films,compared to 3–4 mm on stationary films, which solely relied on gravity for droplet removal. Additionally, flapping films exhibited lower percentage area coverage by water after a few seconds. The second removal mechanism, droplet ejection was analyzed with respect to surface wave formation and inertia. Smaller droplets (e.g., 1-mm diameter) were ejected at a higher frequency which is associated with a higher acceleration. Kinetic energy of the water was the largest contributor to energy required to flap the film, and low energy inputs (i.e., 3.3 W/m2) were possible. Additionally, self-flapping films could enable novel water collection and condensation with minimal energy input.
Citation: X. Chen, N. Doughramaji, A.R. Betz, M.M. Derby, Droplet departure and ejection on flapping films, AIP Advances, 7, 035014.
Keywords: Water vapor; Drop coalescence; Surface dynamics; Thin films; Surface tension